Doping or Deposition of NiS on Cd0.3Zn0.7S Photocatalysts: Optimising Photocatalytic Hydrogen Evolution. Issue 12 (2nd November 2017) - Markovskaya, Dina V.; Kozlova, Ekaterina A.; Cherepanova, Svetlana V.; Kolinko, Pavel A.; Gerasimov, Eugeny Yu.; Parmon, Valentin N.
Abstract: The photocatalytic properties of a Cd0.3 Zn0.7 S photocatalyst modified either by NiS doping or by supporting NiS on the catalyst surface were studied. The obtained samples were investigated by different characterization techniques, including X‐ray diffraction (XRD), UV/Vis diffuse reflectance spectroscopy (DRS), high‐resolution transmission electron microscopy (HRTEM), and X‐ray photoelectron spectroscopy (XPS). The photocatalytic activity was measured in hydrogen evolution from aqueous solutions of Na2 S/Na2 SO3 under visible‐light irradiation ( λ =450 nm). Nickel modifications on the surface and in bulk led to improvements in the photocatalytic activity compared to the pristine sample. The samples modified in bulk underwent changes in composition and an increase of the catalytic activity during illumination was measured. In contrast, the rate of hydrogen photoproduction for the photocatalysts modified by NiS on the surface did not change appreciably. The highest photocatalytic activity values were 11.2 mmol h −1 g −1 and 12.8 mmol h −1 g −1 for the 0.3 % NiS/Cd0.3 Zn0.7 S and Ni0.001 Cd0.3 Zn0.7 S1.001 photocatalysts, respectively. Abstract : Doping is better ! Two series of Cd0.3 Zn0.7 S samples, one in which the bulk was doped with NiS and the other with NiS deposited on the catalyst surface, were prepared. The photocatalysts doped with NiS are more active as a result of new additional energy levels in its band structure (see picture) which can improve photoinduced charge separation and hydrogen photoproduction.